Productos turísticos para diversificar la oferta del turismo en el cantón Chunchi provincia de Chimborazo - Humala Ojeda, Tania Mariela (2017)
Tourism every day acquires an important role in many cantons of the country, becoming a major source in the national economy, generating employment and income for its inhabitants. The present investigation has as its main objective: to design tourism products to diversify the tourist offer of the canton Chunchi Chimborazo province; in the type of research was applied the deductive method where you get general conclusions from particular premises, field research to prioritize the attractions through observation forms in the month of June, filling the new tabs of the tourist inventories by the Ministry of Tourism, documentary research essentially allows the compilation of the sufficient bibliographic material using the proper handling of books, texts, guides, magazines, results of other research related to the topic. The implementation of the survey with the question Would you like to be implement the design of tourism products in the canton Chunchi? It was determined that 95.8% said that if and 4.2% said that no; also analyzed that a 54% want to perform adventure tourism and a 18 % cultural tourism. In the attractions you want to visit tourists is 29% of tourists want the Camino del Inca, 20.3% 18.8% Puñay closed, the waterfall Pailahuayco, 13% goes to the grotto of holy water Pailahuayco ,11.5% visit the Native Forest of Bacun and 7.24% visit the waterfall of Saguan. In this way, we can conclude that the development of tourist packages within the canton Chunchi is necessary; to perform the ranking of attractions we got that 7 are natural attractions with hierarchy II, III and IV and 5 of cultural manifestations, this reflects that the canton has tourist potential to attract domestic and foreign tourists and improve their quality of life on the basis of the tourist activity.